2017
DOI: 10.23887/jere.v1i1.9551
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Authentic Assessment Implementation Based on Curriculum 2013 in SMP Negeri 4 Singaraja

Abstract: This research aimed at (1) describing authentic assessment preparation according to Curriculum 2013 by grade seven teachers in SMP Negeri 4 Singaraja, (2) describing authentic assessment implementation according to Curriculum 2013 (3) describing obstacles experienced by teachers in implementing authentic assessment according to Curriculum 2013 This research is descriptive qualitative study. The data were gaining by study documents, observations, and interview. The result shows that (1) the conformity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…The study by Kartowagiran and Jaedun (2016) also found that the quality of the implementation of authentic assessment in junior high schools in the Special Territory of Yogyakarta still needed improvement because more than half of the teachers did not carry out attitude assessment because: (a) there is no time for conducting attitude assessment in every class meeting, (b) attitude assessment has been conducted by Religion teachers, and (c) the number of the students is too big, both the class size and the number of the students who have to be taught by every teacher, and (d) they do not know how to make instruments and how to carry out attitude assessment. The discrepancy between the design and implementation of assessment is also shown in the finding of the research by Suarimbawa et al (2017) who state that the match between planning and implementing authentic assessment by teachers is in a sufficient category.…”
Section: Discussionmentioning
confidence: 98%
“…The study by Kartowagiran and Jaedun (2016) also found that the quality of the implementation of authentic assessment in junior high schools in the Special Territory of Yogyakarta still needed improvement because more than half of the teachers did not carry out attitude assessment because: (a) there is no time for conducting attitude assessment in every class meeting, (b) attitude assessment has been conducted by Religion teachers, and (c) the number of the students is too big, both the class size and the number of the students who have to be taught by every teacher, and (d) they do not know how to make instruments and how to carry out attitude assessment. The discrepancy between the design and implementation of assessment is also shown in the finding of the research by Suarimbawa et al (2017) who state that the match between planning and implementing authentic assessment by teachers is in a sufficient category.…”
Section: Discussionmentioning
confidence: 98%
“…This situation should be a concern and evaluation material following the implementation scale as stipulated in the Regulation of the Minister of National Education No. 35 of 2010, a scale below 40% indicates that implementation is still not maximal [8]. The development of educational material that could be initiated through the students' opinions during the feedback process [29].…”
Section: Post-assesmentmentioning
confidence: 99%
“…This assessment is based on authentic learning assignments and not a separate test and focuses as much on the process, as is the product [4]. Authentic assessment requires skills implementation that is needed in the classroom and the utilization to support further learning [8,9]. In this assessment, students demonstrate their skills toward an attitude in a real-life context and are assessed based on this fundamental performance [10].…”
Section: Introductionmentioning
confidence: 99%
“…Teacher observations are almost always carried out by teachers to collect student information in class [19]. In addition, teacher observations are used to fill students' daily activities including student attendance, list of activities, and learning material as teacher notes in assessing students [22].…”
Section: "For Student Assessment I Think It's Enough If Everything Is Done By Me Personally If I Involve Students They Also Don't Really mentioning
confidence: 99%